Variability in Interpretation of Magnetic Resonance Imaging of the Pediatric Sacroiliac Joint. Issue 6 (3rd June 2021) - Weiss, Pamela F.; Brandon, Timothy G.; Bohnsack, John; Heshin‐Bekenstein, Merav; Francavilla, Michael L.; Jaremko, Jacob L.; Liao, Lester; McHugh, Anne; Oberle, Edward J.; Rumsey, Dax; Srinivasalu, Hemalatha; Stoll, Matthew L.; et al.
Abstract : Objective: Magnetic resonance imaging (MRI) is pivotal in the assessment of early sacroiliitis in children. We aimed to evaluate the agreement between local radiology reports and central imaging reviewers for active inflammation and structural damage at the sacroiliac (SI) joints. Methods: Eight hospitals each contributed up to 20 cases of consecutively imaged children and adolescents with juvenile idiopathic arthritis and suspected sacroiliitis. Studies were independently reviewed by 3 experienced musculoskeletal pediatric radiologists. Local assessments of global impression and lesions were coded from the local radiology reports by 2 study team members. Test properties of local reports were calculated using the central imaging team's majority as the reference standard. Results: For 120 evaluable subjects, the median age was 14 years, half of the cases were male, and median disease duration at the time of imaging was 0.8 years (interquartile range 0–2). Sensitivity of local reports for inflammation was high, 93.5% (95% confidence interval [95% CI] 78.6–99.2), and specificity was moderate, 69.7% (95% CI 59.0–79.0), but positive predictive value (PPV) was low, 51.8% (95% CI 38.0–65.3). Twenty‐seven cases (23%) had active inflammation reported locally but rated normal at the central reading, 19 (70%) with subsequent medication changes. The sensitivity of local reports detecting structural damage was low, 45.7% (95% CI 28.8–63.4), and specificity was high, 88.2% (95% CI 79.4–94.2); PPV was low, 61.5% (95% CI 40.6–79.8). Conclusion: Substantial variation exists in the interpretation of inflammatory and structural lesions at the SI joints in children. To reliably identify pathology, additional training in the MRI appearance of the maturing SI joint is greatly needed.